Effect of Nitrazepam in Chronic Obstructive Bronchitis. Issue 5815 (17th June 1972) - Gaddie, J.; Legge, J. S.; Palmer, K. N. V.; Petrie, J. C.; Wood, R. A.
Abstract : The effect of nitrazepam on ventilatory capacity and arterial blood gas tensions was studied in a double-blind controlled crossover trial in six patients with chronic obstructive bronchitis in ventilatory failure (raised Paco2 ). Nitrazepam produced a fall in ventilatory capacity and worsening of the ventilatory failure. In the sixth patient, while on the active drug, the Pao2 fell from 48 to 35 mm Hg while the Paco2 tension rose from 59·5 to 68 mm Hg. It is suggested that nitrazepam is contraindicated in patients with severe chronic obstructive bronchitis.